THE EFFECTIVENESS OF SINGING METHODS IN THE DEVELOPMENT OF SPEAKING SKILLS - Resti Marsela resti; Yuniarti (Universitas Darunnajah, 2025)
aims to determine the speaking ability of group A children aged 4-5 years with the singing method at Aisyiyah Bustanul Atfal 3 Kindergarten, Sintang Regency. The research method used is experimental research with quantitative research form. The data sources of this research are tests, observations, and documents. The variables of this study are the Speech Ability Variable (X) and the Singing Variable (Y). The results showed that the implementation of the treatment assessment for three meetings, that in the post-test results of the indicators of children being able to repeat sentences of 4-5 words there are three children who are Very Well Developed, in the second indicator retelling sentences in songs that are sung and listened to there are six children who are Very Well Developed, in the indicator children can answer questions with complex there are five children who are very well developed. The results of the acquisition of the calculated t value of -9.221 with a p-value of 0.001 which is less than the alpha of 0.05, so the decision that can be taken is to rejectHo and acceptHa, meaning that there is effectiveness from the use of singing methods on children's speaking ability. Keywords: Effectiveness, Singing Method, Children's Speaking